1997
DOI: 10.1177/0959353597072002
|View full text |Cite
|
Sign up to set email alerts
|

Discourses of Emotionality in Commercial Sex: The Missing Client Voice

Abstract: This paper analyses the discourse of a group of men who buy sex from women, examining the way they explain and justify their pleasure in such sex. They do so through two sets of interpretations: on the one hand they assert that the commercial exchange is a mutual emotional and sexual relationship between clients and the women who provide sex, and on the other hand they assert that the payment of money discharges all larger obligations associated with relationships. The result is a profoundly self-serving inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 12 publications
0
82
0
1
Order By: Relevance
“…Men's ambivalence about the purchase of women is reflected in the scarcity of research interviews with johns, their desire to remain hidden, and contradictory beliefs about prostitution. In interviews conducted by women prostituting in massage parlors, Plumridge, Chetwynd, Reed, & Gifford (1997) noted that, on the one hand, johns believed that commercial sex was a mutually pleasurable exchange, and on the other hand, they asserted that payment of money removed all social and ethical obligations. White & Koss (1993) observed that violent behaviors against women have been associated with attitudes which promote men's beliefs that they are entitled to sexual access to women, that they are superior to women, and that they have license for sexual aggression.…”
Section: Resultsmentioning
confidence: 99%
“…Men's ambivalence about the purchase of women is reflected in the scarcity of research interviews with johns, their desire to remain hidden, and contradictory beliefs about prostitution. In interviews conducted by women prostituting in massage parlors, Plumridge, Chetwynd, Reed, & Gifford (1997) noted that, on the one hand, johns believed that commercial sex was a mutually pleasurable exchange, and on the other hand, they asserted that payment of money removed all social and ethical obligations. White & Koss (1993) observed that violent behaviors against women have been associated with attitudes which promote men's beliefs that they are entitled to sexual access to women, that they are superior to women, and that they have license for sexual aggression.…”
Section: Resultsmentioning
confidence: 99%
“…First, studies have reported clients' differential motivations and experiences in different commercial sex scenes such as street prostitution (Monto 2000), brothel prostitution (Sanders 2008b), strip clubs (Frank 2002), escort services (Huff 2011) and the increasingly numerous online forums (Earle and Sharp 2007;Milrod and Monto 2012). Second, studies have examined the client-worker relationship, particularly whether clients merely seek sexual release with little emotional involvement or whether they seek affection and companionship (Plumridge et al 1997;Bernstein 2007;Sanders 2008a;Huff 2011;Milrod and Weitzer 2012). Third, studies have adopted a focus on sexual risk and the related public health factors (e.g., Vanwesenbeeck 2001) as well as legal risk and debates concerning whether clients should be prosecuted or not (Sanders 2008b;Serughetti 2012).…”
Section: The Male Client Literaturementioning
confidence: 98%
“…McKeganey and Barnard (1996) identified five major reasons why men buy sex: the capacity to purchase specific sex acts, to have sex with different women, to have sex with women with specific physical characteristics, to enjoy the uninvolved and unemotional contact with sex workers and the fact that buying sex itself is thrilling. Later studies (e.g., Plumridge et al 1997;Campbell 1998;O'Connell Davidson 1998) added other reasons: difficulty finding a partner, being unsatisfied with a current relationship, seeking an emotional connection with sex workers, seeking sex with a particular race or sexual orientation, finding buying sex helps bolster masculinity or finding sex workers an easy target for bullying (for a summary of reasons, see Weitzer 2009, 224 -7;Milrod and Monto 2012, 793 -5;Milrod and Weitzer 2012, 448 -9;Serughetti 2012, 38-40).…”
Section: The Male Client Literaturementioning
confidence: 99%
“…There is also a small body of qualitative research that attempts to understand men's subjective experience of purchasing sex (Holzman and Pine, 1982;Plumridge et al, 1997;Bernstein, 2001;Sanders, 2008;Huysamen and Boonzaier, 2015). The bulk of this research similarly focuses on the customers of indoor workers and again privileges the experiences and worldviews of middleclass men who desire intimacy and regular relationships with sex workers in off-street locations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While these men are willing to acknowledge that they pay for sex, they do not want to experience it as commercial at the time. A key way they are able to maintain this fiction is by focusing on the "mutuality" of the exchange (Plumridge et al, 1997). Men will highlight in their narratives, for instance, the sexual responsiveness of sex workers as evidence of their pleasure and desire.…”
Section: Literature Reviewmentioning
confidence: 99%